The 7 Habits of Highly Effective Families : Building a Beautiful Family Culture in a Turbulent World - Covey, Stephen R. (London Simon & Schuster, 1999)
The long awaited new book by Stephen R. Covey offers precious lessons in creating and sustaining a strong family culture in a turbulent world.
Keywords: Families -- Communication in families -- Parent and child